Loss of FoxOs in muscle increases strength and mitochondrial function during aging. Issue 1 (28th November 2022) - Penniman, Christie M.; Bhardwaj, Gourav; Nowers, Colette J.; Brown, Chandler U.; Junck, Taylor L.; Boyer, Cierra K.; Jena, Jayashree; Fuqua, Jordan D.; Lira, Vitor A.; O'Neill, Brian T.
Abstract: Background: Muscle mitochondrial decline is associated with aging‐related muscle weakness and insulin resistance. FoxO transcription factors are targets of insulin action and deletion of FoxOs improves mitochondrial function in diabetes. However, disruptions in proteostasis and autophagy are hallmarks of aging and the effect of chronic inhibition of FoxOs in aged muscle is unknown. This study investigated the role of FoxOs in regulating muscle strength and mitochondrial function with age. Methods: We measured muscle strength, cross‐sectional area, muscle fibre‐type, markers of protein synthesis/degradation, central nuclei, glucose/insulin tolerance, and mitochondrial bioenergetics in 4.5‐month (Young) and 22–24‐month‐old (Aged) muscle‐specific FoxO1/3/4 triple KO (TKO) and littermate control (Ctrl) mice. Results: Lean mass was increased in Aged TKO compared with both Aged Ctrl and younger groups by 26–33% ( P  < 0.01). Muscle strength, measured by max force of tibialis anterior (TA) contraction, was 20% lower in Aged Ctrl compared with Young Ctrls ( P  < 0.01) but was not decreased in Aged TKOs. Increased muscle strength in Young and Aged TKO was associated with 18–48% increased muscle weights compared with Ctrls ( P  < 0.01). Muscle cross‐sectional analysis of TA, soleus, and plantaris revealed increases in fibre size distribution and a 2.5–10‐fold increase in central nuclei in Young and Aged TKO mice, without histologic signs of muscle damage. Age‐dependent increases in Gadd45a and Ube4a expression as well accumulation of K48 polyubiquitinated proteins were observed in quad and TA but were prevented by FoxO deletion. Young and Aged TKO muscle showed minimal changes in autophagy flux and no accumulation of autophagosomes compared with Ctrl groups. Increased strength in Young and Aged TKO was associated with a 10–20% increase in muscle mitochondrial respiration using glutamate/malate/succinate compared with controls ( P  < 0.05). OXPHOS subunit expression and complex I activity were decreased 16–34% in Aged Ctrl compared with Young Ctrl but were prevented in Aged TKO. Both Aged Ctrl and Aged TKO showed impaired glucose tolerance by 33% compared to young groups ( P  < 0.05) indicating improved strength and mitochondrial respiration are not due to improved glycemia. Conclusions: FoxO deletion increases muscle strength even during aging. Deletion of FoxOs maintains muscle strength in part by mild suppression of atrophic pathways, including inhibition of Gadd45a and Ube4a expression, without accumulation of autophagosomes in muscle. Deletion of FoxOs also improved mitochondrial function by maintenance of OXPHOS in both young and aged TKO.